Автоматизація процесу створення нових цілей у XCODE проєкті - Журба, М.А.; Стеценко, І.В. (Проблеми програмування, 2023)
На сьогоднішній день розробка застосунків під мобільні пристрої стає все більш популярною, але разом з тим більш вартісною. У деяких бізнес-моделях використовуються однотипні застосунки, створені на одній кодовій базі, із впровадженням специфічних відмінностей у дизайні або поведінці для кінцевого продукту. Один із підходів для розробки таких застосунків під iOS полягає у використанні окремих Xcode цілей для кожного продукту. Процес створення нової цілі вимагає проведення ряду рутинних операцій, що потребує витрат часу програміста, а написання коду потенційно схильне до помилок. У даній статті пропонується вдосконалити цей підхід шляхом використання скриптів для генерації проєктного файлу на основі заданих конфігурацій. Розроблено консольний скрипт для генерації проєктного файлу і проєкт для ілюстрації підходу. We live in the era of the Internet and technology. Now it is important for a person to be able to do their routine, uninteresting things quickly, and to be able to focus on more professional things. Everyone wants to minimize the time spent searching for information and have all services in one place. Due to these desires, significant progress is being made in the development of mobile applications. A number of factors also contribute to this. First, the development of the hardware of pocket-sized devices reaches a level sufficient for complex computing tasks. Secondly, the speed of Internet communication has increased. Third, almost everyone in the world now has a smartphone, so it is much more profitable for businesses to develop mobile applications to reach a wider audience. The development of applications for mobile devices is becoming more and more popular, but at the same time more expensive. In some cases, a business needs to have a number of similar applications for one reason or another. There are several approaches to code reuse in the context of iOS development. One is to use a common codebase and separate Xcode targets for each product. The process of creating a new target requires a number of routine operations, which require the programmer’s time, and writing code is potentially error-prone. This research proposes to improve this approach by using scripts to generate a project file based on given configurations. A console script for generating a project file and a project to illustrate the approach have been developed.